Empagliflozin improves chronic hypercortisolism-induced abnormal myocardial structure and cardiac function in mice - Qing-Qing Zhang; Guo-Qing Li; Yi Zhong; Jie Wang; An-Ning Wang; Xiao Zhou; Xiao-Ming Mao (SAGE Publishing, 2020)
Background: Chronic exposure to excess glucocorticoids is frequently associated with a specific cardiomyopathy. Empagliflozin, a sodium-glucose cotransporter 2 (SGLT2) inhibitor, has beneficial effects as it aids in the reduction of heart failure and cardiovascular mortality in hospitalized patients. The aim of this study was to investigate the effects of empagliflozin on chronic hypercortisolism-induced myocardial fibrosis and myocardial dysfunction in mice. Methods: Male C57BL/6J mice (6 weeks old) were randomized to control, corticosterone (CORT), and empagliflozin + CORT groups. After 4 weeks of administration, heart structure and function were evaluated by echocardiography, and peripheral blood and tissue samples were collected. Expressions of Ccl2, Itgax, Mrc1 , and Adgre1 mRNA in heart tissue were evaluated by RT-PCR, and signal transducer and activator of transcription 3 (STAT3) and Toll-like receptor 4 (TLR4) protein expression were analyzed by Western blotting. Results: Empagliflozin effectively reduced body weight, liver triglyceride, visceral adipose volume, and uric acid in CORT-treated mice. Left ventricular hypertrophy and cardiac dysfunction were improved significantly, phosphorylated STAT3 and TLR4 were alleviated, and macrophage infiltration in the myocardium was inhibited after administration of empagliflozin in CORT-treated mice. Conclusion: Empagliflozin has beneficial effects on specific cardiomyopathy associated with CORT, and the results provide new evidence that empagliflozin might be a potential drug for the prevention of this disease.